Mekanisme Penggunaan Closed Circuit Television Sebagai Alat Bukti Petunjuk Dalam Tindak Pidana Pembunuhan - Sarimanella, Michelle Nicole; Adam, Sherly; Leasa, Elias Zadrach (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Closed Circuit Television (CCTV)) is a digital video camera device that is used to transmit signals to a monitor screen in a certain room or place. It has the aim of being able to monitor the situation or condition of a certain place, so that it can prevent the occurrence of a crime or can be used as evidence of a crime that has occurred.Purposes of the Research: Analyze and discuss the mechanism of using CCTV as evidence of evidence in the crime of murder and Knowing the obstacles in using CCTV as evidence of instructions in the crime of murderMethods of the Research: This study uses a normative juridical research method because it uses a literature study that adheres to the juridical aspects with the types of statutory approaches, conceptual approaches, and case approaches.Results of the Research: The results of the study show that CCTV in its mechanism can be used as evidence for instructions in a criminal act, especially a crime of murder, if the CCTV has a link between witness statements, letters, and the defendant's statement as stated in Article 188 Paragraph (2) of the Criminal Procedure Code although there are several obstacles in the evidentiary process such as unclear CCTV footage and different expert views regarding the use of CCTV recordings as evidence for instructions in the process of proving the crime of murder.